Dose devido a incorporação de radionuclídeos pela população do entorno de minas de urânio brasileiras usando dentes como bioindicadores - Guimarães, Viviane Santos (2011)
Possessing one of the largest reserves of uranium, nuclear energy in Brazil has brought great benefits, socioeconomic and technological development. Currently, mining and processing of uranium occurring in Brazil near the city of Caetite uraniferous District of Lagoa Real, Bahia. Several nongovernmental organizations (NGOs) to ensure that uranium mining in this region is clean and causes health risks to the local population, but the leaders of the INB (Nuclear Industries of Brazil), state responsible for complex extraction and production of yellow cake, generator fuel for nuclear power plants in Brazil, denied the accusations. While the actual impacts of uranium mining in Caetité still doubtful, the controversy over the environmental pollution generated by the Brazilian nuclear industry will continue. Therefore, this study aimed to try to identify potential problems caused to the population of Caetité, analyzing samples of teeth of residents of this region have been extracted for orthodontic reasons as biomarkers to quantify the levels of uranium, thorium and potassium incorporated into the body and determine the cumulative dose of radiation in the same samples, thus assessing the degree of radioactive contamination to which this population is exposed. The same analysis was performed in Santa Clover, a town in the state of Ceará that has an untapped reservoir of uranium, and in Aracaju, a place used as a control region, since this location there is no uranium reserve. The concentration of radioisotope was determined by mass spectrometry with inductively coupled plasma (ICP-MS), and doses were estimated from the concentration values and compared to spectra of Electron Paramagnetic Resonance (EPR) samples obtained from teeth. So much for Santa Quitéria as for Caetité, the average concentrations determined were below the reference value, 0.008 ppm, according to UNSCEAR (2008). In samples of the control region was not quantified uranium. The average annual effective dose due to the U found in the three regions studied was below the reference value, according to UNSCEAR (2000), approximately 33 mSv. Therefore, we can t say that the mining process in Caetité brings great harm to the health of the population since the results were similar in the three regions studied.